Reflexivity, Socialization, and Relations to the World: Theoretical and Practical Challenges - Maccarini, Andrea M. (Stan Rzeczy, 2017)
This essay deals with reflexivity and socialization processes in late modernity. First, it is argued that within the societal frame of “unbound morphogenesis” socialization theory is most adequately articulated into a realist-morphogenetic approach, which conceives of socialization as a reflexive, concern-oriented, relational process. However, the so-called morphogenic society involves profound cultural change, impinging upon the idea of the self and its fundamental need to “shape a life.” When such changes are integrated within socialization theory, it becomes clear that different identity-building processes co-exist, including ones that would bring about deep transformations of human reflexivity and challenge its “regular” operation. A brief outline of such a challenge is provided, along the dimensions of personal ontology, time, and sociality. Finally, the need is indicated to develop Archer’s model further, and some provisional conclusions are drawn concerning the possible developmental paths of human personhood depending on these dynamic factors.